Fretting behaviour of galvanised steel - Gaspar, M. C. (2002)
The present work describes research conducted on the fretting behaviour of S 355 MC galvanised steel sheet. In order to study the influence of the normal load and the displacement effect, some of the specimens were galvanised by hot dipping and the rest were only polished before being tested. Fretting tests were carried out on a specially developed fretting rig prototype under [`]crossed-cylinders' contact geometry. Tests were done during 0.72×106 cycles in laboratory air conditions. The tangential force and the displacement were measured in order to establish the fretting cycles for each fretting condition. The fretted surfaces were analysed by means of optical and scanning electron microscopes to identify the main wear mechanisms. Three different fretting regimes were identified: the stick regime; the slip regime; and the mixed stick-slip regime, which depended mainly on the influence of the normal load and the stroke.